Penerapan Instrumen Asesmen Perkembangan Anak Usia Dini Berbasis Taksonomi Solo di TK AL-Huda Kota Gorontalo - Annisa Fahmi Mannassai; Ni Kadek Andriyani; Reva Nesya Hamatia; Paulina Tahir; Dea Ananda Mamonto (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2025)
This study aims to describe the application of SOLO Taxonomy-based early childhood development assessment instruments at Al-Huda Kindergarten in Gorontalo City. The research approach uses a descriptive qualitative method with data collection techniques in the form of observation, interviews, and documentation. The focus of the research includes teachers' understanding of the assessment instruments, the filling process, and the suitability of the instrument application with the principles of SOLO Taxonomy. The results show that the school has implemented four assessment instruments, namely anecdotal notes, checklists, work results, and serial photos as part of formative assessment. In general, the assessment implementation was in line with the children's development, but there was a discrepancy in the use of anecdotal notes, which should have been written one sheet per child but were used for several children at once, thereby reducing the accuracy of the children's development data. The SOLO Taxonomy helped teachers classify the level of complexity of children's understanding from pre-structural to extended abstract, making the assessment more meaningful. This study emphasizes the importance of applying appropriate and individualized assessment instruments so that information on child development is more accurate and can be used to design appropriate follow-up learning activities.